Serious Game-Based Flood Visualization System for Disaster Mitigation Capacity Building - Nur Idil Fitri Idris; Yuliana Yuliana; Rosmini Rosmini (Ceddi Journal of Information System and Technology (JST), 2025)
Flood-prone urban areas continue to face challenges in disaster preparedness due to limited public understanding of flood dynamics and appropriate mitigation responses. Conventional educational approaches often rely on static information that is insufficient to represent rapidly changing flood conditions. This study aims to design and evaluate a serious game–based flood visualization system that serves as an interactive educational medium for disaster mitigation capacity building. The research adopts a structured development approach based on the Game Development Life Cycle, encompassing needs analysis, virtual environment and scenario design, system implementation, and functional and user-based testing. Flood risk conditions are classified using multi-criteria environmental parameters and translated into real-time visual representations within a three-dimensional simulation environment. The results demonstrate that the developed system effectively supports users in recognizing flood behavior, understanding contributing factors, and identifying appropriate mitigation actions. User testing indicates high levels of clarity, engagement, and perceived educational value, suggesting that interactive visualization enhances experiential learning in disaster contexts. This study contributes to disaster education and information systems research by providing a replicable design model that integrates decision-support mechanisms with immersive visualization to strengthen community-level flood mitigation awareness and preparedness.